MENDOAKAN KEBURUKAN KEPADA ORANG YANG ZALIM DALAM PERPSEKTIF ULAMA - Hermansyah (STAI DI AL-HIKMAH, 2023)
Praying evil for wrongdoers has become an important discussion. Because Islam is a religion that is hostile to all forms of injustice. This is because injustice is an action that is detrimental to the person being wronged. Of course everyone will fight against all forms of injustice. One form of resistance to injustice for weak and helpless people is through prayer. And the prayers of those who are persecuted will be answered by Allah. Therefore, what do the scholars think about this act, especially the interpretive scholars? Because there are a number of verses in the Qur'an which indicate that it is permissible to pray evil for unjust people so that their tyranny will be rewarded by Allah Ta'ala or the wrongdoer will stop his tyranny.